From Workshop Participation to Professional Identity: A Single-Case Narrative of an English Teacher - Saka Jaya Arantino; Sumardi; Sri Haryati (Universitas Islam Negeri Palopo, 2025)
Workshops have become an important part of teacher professional development (TPD) in various aspects, particularly in how they impact the development of teachers' professional identity. Despite the numerous studies on Teacher Professional Development (TPD), workshops are under-acknowledged. Therefore, this study aims to explore how the EFL teacher’s experiences through workshop participation influence their professional identity development. Employing a narrative inquiry design, this study explored the single case story data from narrative frames and semi-structured interviews with the emerging theory of Teacher Professional Identity (TPI). Drawing upon the TPI framework (Lu et al., 2024), The findings indicate that workshops enhanced the teacher’s instructional beliefs by broadening pedagogical perspectives, strengthened self-efficacy through increased confidence in instructional delivery, deepened commitment by reinforcing professional motivation, and fostered agency in decision-making and adaptability. These findings not only strengthened the theoretical perspectives from workshop and Teacher Professional Identity (TPI) literature but also extended our understanding of how targeted professional development interventions can support EFL teachers in diverse educational contexts. By demonstrating how workshops contribute to the sustainability of teachers’ professional identity, this study highlights the importance of continuous professional development programs. The findings suggest that well-structured workshops can empower teachers to navigate evolving educational challenges, ultimately improving teaching practices and student learning outcomes. Keywords: EFL Teacher, Narrative Inquiry, Teacher Professional Development, Teacher Professional Identity, Workshop